Analisis Kesalahan Morfologi dalam Berita Online pada Website IDN Times - Erfina Rahayu; Fadhilatur Rosyidah; Nadia Putri Nabhila; Icha Fadhilasari; Arisni Kholifatu Amalia Shofiani5 (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
IDN Times is an Indonesian digital media platform aimed at the younger generation. IDN Times is a journalistic company with two main offices in Jakarta and Surabaya. As a media outlet disseminating news to its readers, IDN Times is not free from language errors in creating and distributing news. The aim of this research is to explain the types of morphological language errors in news writing on IDN Times concerning corruption and the viral fake calculator in the film